Jim Grimsley’s Dream Boy as an Insight into Male Teenage Same-Sex Desire in the American South (American & British Studies Annual, 2017)
The article discusses two opposing interpretations of Jim Grimsley’s novel Dream Boy (1995), a “southern” one and a “gay” one. Because of the ambiguities of the novel, the story of two teenagers, Nathan and Roy, can be considered primarily in its southern setting and understood as an insight into same-sex desire in the South, which often exists outside the categories of gay identity. At the same time, it can be seen as just another coming-out story, this time one set in a rural area and ending prematurely with the violent death of the main protagonist. While the author of the article would subscribe to a “gay” interpretation, he admits that the “southern” interpretation, suggested by Grimsley, may provide a valuable insight into same-sex desire in the American South.
Keywords: American literature; gay literature; southern literature; Jim Grimsley; Dream Boy; rural South in literature; teenage sexuality